PEMANFAATAN TEH SEBAGAI BIOINHIBITOR KOROSI PEGAS DAUN - Nani Mulyaningsih; Sigit Mujiarto; Gyani Ubaydillah (Journal of Mechanical Engineering, 2018)
Leaf springs, especially in cars, are one of the metal components that must get attention because their location under the vehicle causes susceptibility to corrosion due to environmental conditions. Corrosion is an absolute phenomenon that occurs in metals, but corrosion can be controlled by speed with certain techniques. One of them is the use of environmentally friendly corrosion inhibitors (bioinhibitors). Tea is known to have high antioxidant compounds, but its use is only limited as a drink ingredient. Starting from these problems, a study was conducted on the use of tea as a bioinhibitor in leaf pegs. This study use variations in inhibitor concentration (15%, 20%, 25%). To determine the corrosion rate a corrosion test was carried out. The test results showed that tea proved to be able to reduce the highest corrosion rate at concentration  25% in the amount of .37%. Corrosion rate before being given an inhibitor of 3.8195 mm / y and after being given inibitor decreased to 3.4614 mm / y.